2007
DOI: 10.1167/iovs.06-1280
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in the Retinal Mitochondria of Diabetic Mice: Possible Protection by Superoxide Dismutase

Abstract: Retinal mitochondria experience increased oxidative damage in diabetes, and complex III is one of the sources of increased superoxide. MnSOD protects the retina from diabetes-induced abnormalities in the mitochondria and prevents vascular histopathology, strongly implicating the role for MnSOD in the pathogenesis of retinopathy in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
273
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 288 publications
(301 citation statements)
references
References 34 publications
(59 reference statements)
19
273
2
4
Order By: Relevance
“…Diabetes results in mitochondrial defects in multiple tissues including the retina, and prominent among these abnormalities is the increased generation of superoxide (1,4,5,11,17,(38)(39)(40). We previously reported that mitochondria are major contributors to diabetes-induced generation of superoxide by retina (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes results in mitochondrial defects in multiple tissues including the retina, and prominent among these abnormalities is the increased generation of superoxide (1,4,5,11,17,(38)(39)(40). We previously reported that mitochondria are major contributors to diabetes-induced generation of superoxide by retina (11).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of oxidative stress by feeding antioxidants or overexpressing antioxidant enzymes has reduced diabetes-induced degeneration of retinal capillaries (3)(4)(5)(6)(7). Moreover, oxidative stress has been reported to regulate expression of proinflammatory proteins (8)(9)(10), which also have been shown to play a critical role in the pathogenesis of this early retinopathy (2).…”
mentioning
confidence: 99%
“…It appears to be causally involved in the development of the retinopathy as oral administration of antioxidants 17 or genetic overexpression of superoxide dismutases 18 has been shown to inhibit the diabetes-induced degeneration of retinal capillaries in animal studies. Moreover, up-regulation of ROS can lead to increased activation of NF-kB, which, in turn, increased the release of proinflammatory cytokines and nitric oxide (NO).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Mitochondrial superoxide are considered as the unifying molecules connecting many metabolic abnormalities associated with diabetic retinopathy [7,67,68], and in diabetes, retinal mitochondria are damaged and superoxide scavenging enzyme (superoxide dismutase) is dysfunctional [69]. We have shown that diabetes epigenetically modifies Sod2, the gene encoding mitochondrial superoxide dismutase, and H4K20me3, acetyl H3K9 and p65 subunit of NF-B (p65) are increased at its promoter/enhancer, H3K4 is demethylated and LSD1 binding is increased.…”
Section: Epigenetic Modification and Diabetesmentioning
confidence: 99%